Aggregation in Black Soils as Related to their Physical and Chemical Properties - Kauraw, D. L.; Verma, G. P.; Tiwari, V. D. (Indian Forester, 1974)
The extent of aggregation in black soils belonging to different categories of toposequence was found to vary widely and it was comparatively greater in deep black clayey soil under haveli system of cultivation. On working out a correlation between various indices of aggregation and the important physical and chemical properties of these soils, clay fraction was found to be more important for the formation of water stable aggregates as compared to organic matter. Also, percentage of aggregates was found to be positively and significantly related to cation exchange capacity and increased with increasing concentration of exchangeable calcium and Potassium.